Pills and the damage done: the opioid epidemic as man-made crisis - McDonald, Rebecca; Eide, Desiree; Skurtveit, Svetlana; Clausen, Thomas (Frontiers in Public Health, 2024)
The prescription opioid epidemic has slowly evolved over the past quarter century with increasingly detrimental consequences for public health. Man-made crises are often unforeseen and characterized by a situation without natural causes where – because of human intent, error, negligence, or the failure of manmade systems – the level of needs in the population exceeds available resources to counter the problem. This paper presents the prescription opioid epidemic as a man-made crisis and explores the public health impact of opioid manufacturers and other industries producing commodities with addictive potential as a shared vulnerability among countries. We examine this concept within the framework of the commercial determinants of health. We address three key aspects of the commercial determinants of health: (1) Cross-industry mechanisms, (2) policy inertia, and (3) the role of industry in science. Within cross-industry mechanisms, we explore parallels between prescription opioid epidemic and unhealthy commodity industries in terms of marketing, corporate use of misinformation, and diversionary tactics. Next, we examine how policy inertia has dominated the slow response to this man-made crisis. Lastly, we discuss how results from clinical trials are used as a key marketing strategy for drugs. The origins of the prescription opioid epidemic may be traced to innovations in drug development with the promise of improved pain management. However, through multiple factors, including fraudulent marketing from pharmaceutical industry and policy inertia, the resulting crisis represents a multi-system failure of regulation exploited by corporate greed.